Energy, exergy, and emission analysis of modified compression ignition engine working on triple fuel mode - Vardhan, Ajay; Chandra Tiwari , Aseem; Ahirwar , Rekha (CT&F - Ciencia, Tecnología y Futuro, 2023)
For the past few years, the energy demand has been raised progressively all over the world. Numerous extensive studies have been conducted to reduce the rate of emission in diverse alternative fuels. However, currently numerous investigations have been undertaken to diminish the harmful impact of the exhaustion of gas emissions from the utilization of diesel, Liquefied Petroleum Gas (LPG), and gasoline fuels. Hence, a novel triple fuel system (i.e. petrol, diesel, and LPG) is proposed based on three different analyses, namely energy, exergy, and emission at diverse load (kg) conditions. Nonetheless, the validations of each method are performed by single-cylinder four-stroke diesel engines at optimized conditions. Moreover, the analyses are performed at a constant speed rate of 1500rpm, with six diverse engine loads (kg) of about (2.5, 5, 7.5, 10, 12.5, and 13.50 kg). Various measurable factors such as emission rate, heat transfer rate, and cylinder pressure are determined to estimate the steady state condition. Finally, various parameters such as brake thermal efficiency, specific fuel consumption, and exhaust gas analysis are performed and compared with single fuel, dual fuel, and the proposed triple fuel modes to determine the efficiency of the system.